Review on the Impacts of Community-Based Ecotourism on Household Financial Asset Improvement and Its Determinants in Ethiopia - Melsew Nibret Mazengiya (Advances in Agriculture)
Community-based ecotourism has been recognized as an important factor for households’ livelihood. Rural households normally have a problem of getting access to participate in ecotourism activities and making family better livelihood status in rural areas. The paper was aimed to review the impacts of community-based ecotourism on household financial asset improvement and its determinants in Ethiopia. Community-based ecotourism has been contributing to employment and income-generating activities. To achieve this objective, the published journal articles and reports were reviewed. As empirical review indicates that, institutional factors such as access to training and distance to the park, economic factors such as annual income, and demographic factors determine the participation of households in community-based ecotourism in Ethiopia. Therefore, the tourism extension expert should create awareness for local communities towards participation in community-based ecotourism in Ethiopia.